IMPLEMENTASI PERATURAN GUBERNUR RIAU NOMOR 109 TAHUN 2015 TENTANG PENYELENGGARAAN PENYEDIAAN RUANG KHUSUS MENYUSUI DI TEMPAT SARANA UMUM DI KOTA PEKANBARU - Ilham, M.; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Breastfeeding special room is one of the government programs to increase Exclusive breastfeeding and to support high maternal mobility. Provision of Breastfeeding Special Room program is written in Riau Governor Regulation No. 109 of 2015. The regulation affirms that the government provides protection to mothers in providing exclusive breastfeeding to their baby and enhances the roles and support of families, communities, Provincial Governments and the private sector to exclusive breastfeeding.Therefore, to raise the awareness of mothers about the importance of exclusive breastfeeding, one of the ways that can do is to provide a room that can support the mother to breastfeed comfortably and privacy. But the results show that the implementation of this policy implementation has not run maximally. Although regulations have been issued on the obligation of every public facility to provide a special room for breastfeeding mothers in Riau Governor Regulation No. 109 of 2015, but the application of Special Provision of Breastfeeding in the field is still very low and has not been supervised by the government.Suggestions for related institutions, improvement of socialization activities to the policy objectives and improving supervision on the provision of breastfeeding special room in public facilities, especially in Pekanbaru City and crack down on public facilities that have not yet provide special room for breastfeeding.Keywords: Implementation, Breastfeeding Room, and Place of public facilities.